Evaluation of Sutureless, Glueless, Flapless, Intrascleral Fixated Posterior Chamber Intraocular Lens in Children with Ectopia Lentis. (29th August 2018) - NB, Kannan; Kohli, Piyush; Pangtey, Bhanu Pratap Singh; Ramasamy, Kim
Abstract : Aim . This paper aims at evaluating refractive outcome and complication profile of sutureless, glueless, flapless, intrascleral fixation of intraocular lens (SFIOL) in pediatric population. Methods . This retrospective study included patients ≤18 years of age who underwent SFIOL for ectopia lentis. Details obtained included preoperative uncorrected visual acuity (UCVA), cycloplegic refraction, and best-corrected visual acuity (BCVA); intraoperative complications; and postoperative UCVA, cycloplegic refraction, and BCVA and complications. Results . Median pre- and postoperative UCVA was logMAR 1.78 (Snellen 20/1200) and logMAR 0.30 (Snellen 20/40), respectively, (p < 0.001 ). Median pre- and postoperative BCVA was logMAR 0.24 (Snellen 20/34) and logMAR 0.18 (Snellen 20/30), respectively. UCVA ≥20/60 was attained in 90% of eyes. BCVA ≥20/30 was attained in 85.0% of eyes. Most common early postoperative complications were hyphaema (10%), transient vitreous hemorrhage (2.5%), and ocular hypotony (2.5%). None of these developed any long-term sequelae. Only one case of subluxation of IOL was seen. No case of late endophthalmitis or retinal detachment was seen. Conclusion . Since refractive error induced is minimal, the procedure is suitable for IOL implantation in children, who are noncompliant with spectacles. The complication profile is similar to that reported in adults.